The Effects of Brain Mind and Learning Training Program on Executive Functions of the Brain of Primary School Students - พาหิรัญ พัชรินทร์; แหนจอน จุฑามาศ; ศิริธาดากุลพัฒน์ ศศินันท์ (Ratchaphruek Journal, 2018)
The research aimed to study the effects of brain, mind and learning training (BMLT) program on executive functions of the brain in primary school students. The sample consisted of 40primary students at Wat Nongk or Community School in the academic year of 2017. The samples were divided by simple random sampling in to 2 groups; the experimental group and the control group. Each group consisted of 20 students. The research instruments were the BMLT program, and the Wisconsin Card Sorting Test (WCST-64). The data collection was divided into three phases; the pretest, the posttest, and the follow-up phase. The research was conducted in 9 sessions, two times a week. Each session lasted for 50 minutes for the experimental group; the control group joined the regular school’s activities. The data were analyzed by repeated measures of variance: one between-subjects variable and one within-subjects variable followed by paired-different test by Bonferroni. The results of the study indicated that; 1) there was statistically significant interaction at .05 level between the method and the duration of experiment, 2) the students in the experimental group had higher mean score of total correct than the students in the control group, in the posttest and the follow-up phases statistically significance different at .05 level, and 3) the students in the experimental group had higher mean score of total correct in the posttest phase, and the follow-up phases than the pretest phases with statistically significance different at .05 level. It was concluded that the BMLT program was effective in enhancing the executive functions of primary school students’ brain.